Clinical relevance of HEp-2 indirect immunofluorescent patterns: the International Consensus on ANA patterns (ICAP) perspective. Issue 7 (12th March 2019) - Damoiseaux, Jan; Andrade, Luis Eduardo Coelho; Carballo, Orlando Gabriel; Conrad, Karsten; Francescantonio, Paulo Luiz Carvalho; Fritzler, Marvin J; Garcia de la Torre, Ignacio; Herold, Manfred; Klotz, Werner; Cruvinel, Wilson de Melo; Mimori, Tsuneyo; von Muhlen, Carlos; et al.
Abstract : The indirect immunofluorescence assay (IIFA) on HEp-2 cells is widely used for detection of antinuclear antibodies (ANA). The dichotomous outcome, negative or positive, is integrated in diagnostic and classification criteria for several systemic autoimmune diseases. However, the HEp-2 IIFA test has much more to offer: besides the titre or fluorescence intensity, it also provides fluorescence pattern(s). The latter include the nucleus and the cytoplasm of interphase cells as well as patterns associated with mitotic cells. The International Consensus on ANA Patterns (ICAP) initiative has previously reached consensus on the nomenclature and definitions of HEp-2 IIFA patterns. In the current paper, the ICAP consensus is presented on the clinical relevance of the 29 distinct HEp-2 IIFA patterns. This clinical relevance is primarily defined within the context of the suspected disease and includes recommendations for follow-up testing. The discussion includes how this information may benefit the clinicians in daily practice and how the knowledge can be used to further improve diagnostic and classification criteria.